PENGARUH KUALITAS LAYANAN, FITUR LAYANAN APLIKASI DAN HARGA TERHADAP LOYALITAS PELANGGAN JASA MAXIM BIKE DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI DI KOTA PADANG - Nur Hapizah; Yulia Hendri Yeni (Halu Oleo University, 2024)
This online transportation service business makes it easier for people to carry out various activities in their daily lives. Online transportation usually uses an application platform on a mobile phone and utilizes internet technology to run it. This research aims to determine the influence of Service Quality, Application Service Features and Tariffs on Maxim Bike Service Customer Loyalty with Customer Satisfaction as a Mediating Variable. An online survey was conducted on 120 respondents. The research instrument was adapted from previous research. Structural equation modelling was applied to analyze this research data using SmartPLS 4.0 software. The research results show that service quality and rates have an important and meaningful impact on customer loyalty. The impact of service quality and rates on customer loyalty is significant. However, the application service features do not have a significant influence on customer loyalty and customer satisfaction with Maxim Bike services.